(untitled) (Advancements in Homeopathic Research, 2025)
The word ‘Obesity’ came from Latin word; where the verb ‘obedere’ means ‘over eat’ and ‘obesitas’ means ‘being very fat’. Obesity is a health condition in which the natural energy stored, reserved in the fatty tissue of human beings, is increased to that point where it is linked with certain health issues. It can be defined in relative or absolute terms. Practically, it is evaluated in absolute terms by measuring BMI (body mass index), but also in terms of its distribution through waist circumference or waist-hip circumference ratio measurements. The normal amount of body fat (expressed as percentage of body fat) is between 26-30% in female and 19-24% in male. Female with over 30% body fat and male with over 25% body fat are considered as obese. Women of reproductive age have higher rates of overweight and obesity and are more adversely affected by obesity-related complications than men. This gender difference is mainly due to general weight gain during childbearing years, gestational weight gain and weight retention, adverse lifestyle, or risk factors associated with pregnancy and the postpartum period. Maternal obesity increases the risk of numerous complications including pregnancy, labour and birth for both the mother and the child, diabetes and hypertensive disorders etc. Compared with normal weight, maternal overweight is associated with a higher risk of caesarean delivery and a higher incidence of anaesthetic and postoperative complications. Low Apgar scores, macrosomia and neural tube defects are also more frequent in infants of obese mothers compared with infants of normal weight mothers. Obesity may be caused by a number of social, cultural, behavioral, physiological, metabolic, and genetic factors that are beyond the person’s control. Obesity is most commonly caused by a combination of excessive food energy intake, lack of physical activity, and genetic susceptibility, although a few cases are caused primarily by genes, endocrine disorders, medications or psychiatric illness. It is associated with increased risk of medical illness, disability, and death. It is a metabolic disorder that is primarily induced and sustained by an over consumption and underutilization of caloric substrate.